Analisis Model Mental Dengan Pendekatan Problem Posing Berbasis Representasi Kimia - Asni, Taufiqurrahman (LPPM Universitas Negeri Jakarta, 2024)
This research was conducted to apply the Problem Posing learning model integrated with chemical representations to analyze the improvement of mental models and student learning outcomes in the material of basic chemical laws. This study aims to find out (1) how students' mental models are applied after applying the Problem Posing learning model integrated with chemical representations in basic chemical law material (2) how to improve students' cognitive learning outcomes through the Problem Posing model. The method in this study used classroom action research (CAR) carried out in cycles. The research subjects were students of class X IPA 1 SMA Negeri 1 Sungai Tabuk, totaling 26 students. The research instrument used was a test and non-test. The data collection technique used tests, namely the cognitive learning outcomes of students using instruments in the form of pre-test and post-test, while non-test data collection techniques, namely observation sheets of teacher activities and student activities. The mental model data analysis technique used is descriptive qualitative analysis technique. The results of the study show that (1) Through the Problem Posing learning model, students experience changes in mental models, meaning that the application of Problem Posing learning can train students' reasoning power in understanding the material so that students do not experience continuous misconceptions, (2) there is an increase in learning outcomes cognitive class X IPA 1 students with an average pre-test score of 28.83% and an average post-test score of 79.75% after applying the Problem Posing learning model